DNA replication in Physarum polycephalum: bidirectional replication of DNA within replicons. - Funderud, S (1978)
The direction of replication of DNA within replicons of Physarum polycephalum was studied by pulse-labelling with 5-bromouracil-deoxyriboside (BrdUrd) and 3H-adenosine deoxyriboside (dAdo), followed by ultraviolet- (UV) -photolysis and analysis of molecular weights of single strand DNA fragments on alkaline sucrose gradients. Newly made DNA within replicons at all stages of completion is split in two equal halves upon UV irradiation when BrdUrd was given at the time of initiation of DNA synthesis. This shows that replication within replicons of Physarum polycephalum starts at an origin located in the center of each unit, proceeding bidirectionally from this origin.